Determinan perilaku konsumsi tablet tambah darah pada mahasiswi jurusan kesehatan dan nonkesehatan di Universitas Jember - Dzati, Yasmin Ihza Aula; Ningtyias, Farida Wahyu; Rohmawati, Ninna (Jurnal Gizi Klinik Indonesia, 2024)
Determination of iron supplement tablet consumption in health and non-health majors at Jember UniversityBackground: Iron tablet supplementation is an important strategy in preventing anemia in adolescent girls. The 2018 Riskesdas RI data shows that 23.8% of young women have not received and consumed iron tablets. In female college students, iron supplement consumption can be influenced by several determinant factors, such as knowledge and social support.Objective: This study aims to analyze the determinants of behavior in female college students when consuming iron tablets.Methods: This is an analytical observational research study with a cross-sectional design. Using the proportional random sampling technique, the sample size was 336 female students majoring in health and non-health at the University of Jember. Due to restrictions during the COVID-19 pandemic, data was collected online via Google Forms and in-person interviews. The independent variables are the level of knowledge, family, and peer social support. The dependent variable is the consumption behavior of iron tablets. Data analysis used Spearman's rho test.Results: Respondents from the health department (88.9%) and non-health (73%) had good knowledge. Family and peer support for health and non-health respondents was lacking. Respondents majoring in health (35.2%) and non-health (8.5%) did consume iron tablets regularly. The determinant factor that was significantly related (p<0.05) to the consumption behavior of ironic tablets in health majors was material support from the family (p=0.01). The determinant factors that were significantly related (p<0.05) to the consumption behavior of iron tablets in non-health majors are knowledge (p=0.032), family social support (p=0.00,) and peer support (p=0.00).Conclusions: Determinant factors of TTD consumption behavior were found to be different between female students majoring in health (material support from family) and non-health (knowledge, family social support, and peer support).